Pengaruh Pembelajaran Pendidikan Agama Islam Berbasis Praktikum Sederhana Terhadap Keterampilan Proses Sains Siswa Sekolah Dasar - Soraya, Arafatul; Nasution, Asrin; Marwah, Marwah; Lubis, Namiroh (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This study aims to investigate the effect of a simple practicum in Islamic Religious Education (PAI) learning on science process skills and abilities.Islamic Religious Education (PAI) on science process skills and critical thinking ability of elementary school students. critical thinking skills of elementary school students. The method used was a quasi-experiment with pre-test and post-test design, involving two groups: an experimental group thaatt participated in the simple practicum and a control grout who learned with traditional methods. The results showed that the experimental group experienced significant improvement in science process skills, with an average pre-test score of 58.3 increasing to 82.7 in the post-test. Meanwhile, the control group only increased by 16.4%. The questionnaire showed that students felt that the simple practicum helped them understand science concepts (average score 4.6) and increased interest in learning science (score 4.7). In addition to In addition, the practicum also contributed positively to the development of students' critical thinking skills (mean score 4.4). This finding supports constructivist learning theory, which emphasizes the importance of hands-on experience to increase students' cognitive engagement. to enhance students' cognitive engagement. Overall, this study shows that simple integrated practicum in learning is effective in improving students' understanding of science concepts and students' critical thinking skills, thus becoming an effective method in science science education in elementary school.